Improving Strength of Porous Asphalt: A Nano Material Experimental Approach - Rani Pradoto; Eliza Puri; Tri Hadinata; Qinthara D Rahman; Ryan Muhammad Az-zuchruf (Civil Engineering Departement, Andalas University, 2019)
Porous asphalt (PA) has potential to be utilized in many urban area in Indonesia which often faced high street runoff during rainy season. PA can be a solution for storm water management. A typical porous pavement has an open-graded surface over an underlying stone recharge bed. The water drains through the porous asphalt and into the stone bed, then, slowly, infiltrates into the soil. However, despite of the benefit of porous asphalt, there is still weaknesses, such as less of service life than dense-graded asphalt due to its lower durability and strength. In order to improve durability and strength of PA, this study investigates the effect of utilizing fly ash (FA) class F in porous asphalt (PA) mixture as replacement in aggregate gradation and perform as filler. Mechanical activation (grinding) of fly ash was performed resulting in reduction of particle size. This material gives more strength since the more of surface area that can bind in finer particle size. Utilizing fly ash into nanomaterial is one of the methods for this study. Material approaches for nanomaterial were proposed by breaking up larger particles with physical processes such as grinding or milling. This is called mechanical activation. Since asphalt pen 60/70 is mainly binder material in Indonesia, it is used as the default for all samples in this experiment. The optimum bitumen content (OBC) was determined for all the mix by Marshall mix design. In view of the nanomaterial approach, samples were then prepared for the same optimum bitumen content (5.85%) by using Bina-Marga’s PA standard in control mix as well as natural FA and modified FA as alternative filler in modified mixes. modified FA itself has been milled using transversal ball mill machine for 3 to 6 hours. This experimental study indicated higher stability value and reduction of permeability with the same OBC for the mixture having modified FA as filler content in comparison with standard mix and natural FA mix. All sample conformed with Indonesian asphalt porous Specification. This trends will become as a starting point for improvement in the future research. For further research, binder modification with added material such as rubber or nanoparticles are highly recommended to improve strength and durability of asphalt porous. However, another method need to be proposed for reduction of particle size in fly ash into nanomaterial range.